"Surviving the storm through the shelter of Ayurveda" - International webinar on integrated approach to combat COVID-19 - A conference report - Tanuja Manoj Nesari; Mahesh Vyas; Meera K Bhojani; Shivakumar S Harti; Arun Kumar Mahapatra; Aparna Dileep; K P Karthik (Wolters Kluwer Medknow Publications, 2021)
COVID-19 has put forward a conundrum that needs to be addressed together by every system worldwide. Traditional medical systems need to be incorporated to the battle against COVID. The time-tested and experiential wisdom in these streams of knowledge are to be utilized.. All India Institute of Ayurveda, New Delhi, took one of the initial steps in this respect, bringing together the exponents of Ayurveda all over the world to contribute their ideas in understanding, preventing and managing COVID-19. The meeting was conducted on May 5, 2020, 3:00 p. m. and included representatives from the Ministry of AYUSH, the national institutes, research bodies, and international organizations of Ayurveda. The program had six sessions, which encompassed the current understanding of the disease, the clinical presentations, Ayurvedic analysis of the same, methods of salutogenesis, disease prevention and cure that can be implemented in this scenario, and considerations while applying the Ayurvedic wisdom to other parts of the world. The meeting was broadcasted live on Facebook as well as YouTube.